Peran Kegiatan Kewirausahaan dalam Meningkatkan Soft skill Mahasiswa di Era Globalisasi - Nadiyah Salamah; Marsela Marsela; Naela Faiza Khaerani; Karyadi Hidayat (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This article discusses how entrepreneurial activities can enhance students' soft skills in the context of globalization, with an emphasis on communication, leadership, and adaptability. The study employs a descriptive qualitative method, utilizing literature review techniques that allow for a narrative exploration of soft skill development such as communication and leadership in entrepreneurial activities. The analysis reveals that entrepreneurial engagement significantly improves students' soft skills, including teamwork collaboration and innovation, which are essential for facing the challenges of globalization. The findings suggest that practice-based entrepreneurship education is far more effective than theory alone in building resilience and networks. The study concludes by highlighting the importance of integrating entrepreneurial activities into higher education curricula to prepare students for global competition, along with recommendations to develop project-based programs. This research contributes to the higher education literature with empirical evidence derived from the Indonesian context, although it is limited to a specific group of students.